2013
DOI: 10.1007/s00586-013-2927-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in a rat model of neurogenic bladder, effect of statins and phosphodiesterase-5 inhibitors

Abstract: Purpose Neurogenic bladder is a common complication of several central nervous system injuries. Statins and phosphodiesterase-5 (PDE-5) inhibitors are reportedly beneficial in neural injuries and urinary system dysfunction. The effect of simvastatin, sildenafil and tadalafil on several renal function indices of an animal model of neurogenic bladder was investigated. Methods Forty male rats were assessed in five equal groups. Dura mater and the cord were injured with an aneurysmal clamp at the level of T9-T10 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Upper urinary tract deterioration due to NB represents the final stage of disease, which poses a challenge for treatment. However, there are few studies examined the effects of neurorrhaphy on kidney function . Our study tries to reveal some aspects of neurorrhaphy particularly its effects on restoration of bladder function in an animal model of NB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper urinary tract deterioration due to NB represents the final stage of disease, which poses a challenge for treatment. However, there are few studies examined the effects of neurorrhaphy on kidney function . Our study tries to reveal some aspects of neurorrhaphy particularly its effects on restoration of bladder function in an animal model of NB.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this knowledge, there are only few studies that reveal how NB affects renal morphology and function and how renal injury caused by NB can be protected in animal models. Mirzaii‐Dizgah and Salmanyan found that statins effectively improve the renal morphology and function in a condition of renal dysfunction in a rat model of NB, which is achieved through drug treatment. To our knowledge, this is the first time that end‐to‐side neurorrhaphy, a surgical procedure, is used to treat NB and attempts to prevent renal deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of neurogenic bladder, Mirzaii-Dizgah and Salmanyan [25] assessed 40 male rats divided into five equal groups. SCI was induced in all but the sham group, and renal system and motor functions were evaluated 28 days following injury.…”
Section: Evidence Synthesismentioning
confidence: 99%